How Cultural Frames Guide Strategies to Eliminate Child Hunger. Issue 1 (2nd January 2020) - Jones, Sonya J.; Craig, Jason D.; Younginer, Nicholas; Whitt, Olivia; Childers, Casey; Draper, Carrie; Freedman, Darcy A.; Blake, Christine E.; Liese, Angela D.
ABSTRACT: Cultural frames, or myths we use to communicate, shape how we understand social problems, such as child hunger. In 48 interviews, we identified metaphors and myths, such as "the poor will always be with you, " "meat product, " and "butterfly effects" that point to cultural frames of child hunger. Three different frames were identified – the welfare state, the free market, and the resilience and resistance frame. Speakers used frames to communicate different types of social responsibility for hunger. Understanding which frames we invoke with our stories may allow for more effective collaborative action to end child hunger.